Presence of pathogenic copy number variants (CNVs) is correlated with socioeconomic status. Issue 1 (23rd September 2019) - Burghel, George J; Khan, Unzela; Lin, Wei-Yu; Whittaker, William; Banka, Siddharth
Abstract : Socioeconomic status (SES) is a major determinant of health. We studied the Index of Multiple Deprivation Rank of 473 families with individuals with pathogenic autosomal copy number variants (CNVs) and known inheritance status. The IMDR distribution of families with pathogenic CNVs was significantly different from the general population. Families with inherited CNVs were significantly more likely to be living in areas of higher deprivation when compared with families that had individuals with de novo CNVs. These results provide unique insights into biological determinants of SES. As CNVs are relatively frequent in the general population, these results have important medical and policy consequences.